Criminal Policy as an Instrument for Controlling Criminal Acts Based on Restorative Justice - Nasution, Shulhan Iqbal (Rechtsvinding, 2025)
Criminal policy in Indonesia plays an important role in crime control efforts, but the dominant approach, namely retributive, has not been able to resolve the roots of social problems and restore victims' rights comprehensively. The research method used is normative juridical or library research, by analyzing library materials or secondary data that are relevant to the topic. This research is descriptive analytical, namely the data obtained and processed and analyzed to provide a comprehensive picture of criminal policy functioning as an instrument for controlling criminal acts based on restorative justice with data collection methods through document studies and interviews. Research Results Show that Criminal Policy in Indonesia has not been able to resolve the root of social problems and restore victims' rights comprehensively. Therefore, a more humanistic and participatory policy reformulation is needed through a restorative justice approach. Restorative justice offers a resolution mechanism that actively involves perpetrators, victims, and the community with the main goal of recovery and reconciliation. Although its implementation has begun through a number of internal policies of law enforcement institutions, its implementation still faces structural and normative challenges. Optimizing this approach requires strengthening regulations, increasing the capacity of officers, and shifting the legal culture from an orientation towards revenge towards just social recovery